USING VIDEO MATERIALS IN LESSONS FOR B1 LEARNERS (Modern education and development, 2025)
This paper explores the effectiveness of incorporating video materials into lessons for B1-level English learners. As learners at this intermediate level often struggle with maintaining motivation and improving listening comprehension, authentic and pedagogically adapted videos serve as powerful tools to enhance engagement and language acquisition. The study examines various types of video content such as short films, interviews, and instructional videos and their impact on vocabulary development, listening skills, and cultural awareness. The paper concludes with recommendations for teachers seeking to optimize video use in communicative and learner-centered classroom environments.